2018
DOI: 10.3329/bjms.v17i3.37002
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in case finding of tuberculosis control program in Iran: A qualitative study

Abstract: Introduction: weakness in case finding and delays in diagnosing patients with smear-positive pulmonary tuberculosis are considered as important factors in spreading disease. According to reports available in some parts of Iran, there is a long delay in diagnosing patients, and case finding level is less than the level predicted by Global Tuberculosis Control Program. Thus, this research was carried out to identify challenges of diagnosing tubercular patients in the framework of Iran's tuberculosis control prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…In our setting, accountability relationship was enhanced by programme management support, supportive supervision and quarterly performance review meetings. Nevertheless, the weak stewardship from the LG confirms previous evidence that TB control program is perceived as less important than other public health programmes [20,23] but contrasts evidence of strong political commitment from district governments in Pakistan [8]. Unmet expectation of local officials of financial incentives from NTP and perception that partners support TB control explained low responsiveness of LGs.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…In our setting, accountability relationship was enhanced by programme management support, supportive supervision and quarterly performance review meetings. Nevertheless, the weak stewardship from the LG confirms previous evidence that TB control program is perceived as less important than other public health programmes [20,23] but contrasts evidence of strong political commitment from district governments in Pakistan [8]. Unmet expectation of local officials of financial incentives from NTP and perception that partners support TB control explained low responsiveness of LGs.…”
Section: Discussionsupporting
confidence: 60%
“…This study's findings revealed that poor human resources management practices and inadequate training of TB service providers hindered TB control. These findings are consistent with lack of skilled staff [4,10,11,22]; lack of incentives for TB service providers [5,10]; inadequate training [10,11,19]; and poor attitude and weak commitment of health workers towards deployment to TB services [22,23]. In contrast, evidence from European countries show that skilled and motivated healthcare workers enabled TB control [16].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Based on the other results obtained from the both mentioned regions, the rate of MDR is about the same amount was reported. [17][18][19][20] .…”
Section: Drug Susceptibility Testmentioning
confidence: 99%